2017
DOI: 10.1016/j.dsr2.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, abundance and habitat use of deep diving cetaceans in the North-East Atlantic

Abstract: In spite of their oceanic habitat, deep diving cetacean species have been found to be affected by anthropogenic activities, with potential population impacts of high intensity sounds generated by naval research and oil prospecting receiving the most attention. Improving the knowledge of the distribution and abundance of this poorly known group is an essential prerequisite to inform mitigation strategies seeking to minimize their spatial and temporal overlap with human activities. We provide for the first time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 77 publications
(71 reference statements)
10
66
0
Order By: Relevance
“…In the Mediterranean Sea, our predictions were consistent with the documented presence of beaked whales and sperm whales in the Alborán, Tyrrhenian and Ligurian Seas (Arcangeli, Campana, Marini, & MacLeod, ; Cañadas et al, ; Lanfredi et al, ; Praca & Gannier, ) and along the eastern coasts of the Mediterranean Sea (Podestà et al, ). In the North Atlantic Ocean, the highest relative densities of beaked whales and sperm whales were predicted along the slope, a result consistent with those of Rogan et al () and Roberts et al (). In the north‐west Atlantic Ocean, higher relative densities of kogiids were predicted in warmer and deeper waters, which is consistent with their known ecology (McAlpine, ) and the predictions of Mannocci, Roberts, Miller, and Halpin () except for predictions off the coast of Florida.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the Mediterranean Sea, our predictions were consistent with the documented presence of beaked whales and sperm whales in the Alborán, Tyrrhenian and Ligurian Seas (Arcangeli, Campana, Marini, & MacLeod, ; Cañadas et al, ; Lanfredi et al, ; Praca & Gannier, ) and along the eastern coasts of the Mediterranean Sea (Podestà et al, ). In the North Atlantic Ocean, the highest relative densities of beaked whales and sperm whales were predicted along the slope, a result consistent with those of Rogan et al () and Roberts et al (). In the north‐west Atlantic Ocean, higher relative densities of kogiids were predicted in warmer and deeper waters, which is consistent with their known ecology (McAlpine, ) and the predictions of Mannocci, Roberts, Miller, and Halpin () except for predictions off the coast of Florida.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the very low sighting rates of deep‐diving cetaceans, each survey taken separately cannot provide enough data to investigate the habitats of these rare species. In contrast to Rogan et al (), we did not assemble data collected with similar protocols but data collected with different variants of the line‐transect distance sampling protocol, which meant standardizing the data according to their core communalities before developing a single spatial model. Ideally, at a time when shared databases are becoming increasingly important (e.g., OBIS SEAMAP – https://seamap.env.duke.edu/, EMODnet – https://www.emodnet.eu/), implementing standardized survey methods would greatly improve data compatibility, by enhancing the level of communalities in shared datasets, and helping to describe large‐scale habitats and distributions of marine species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Oudejans , Rogan et al . ). Despite the information compiled in these studies, knowledge on the ecology of True's beaked whales is poorly known and usually gleaned from the small number of strandings.…”
Section: Prey Species Identified From Both Adults and The Calf Of Trumentioning
confidence: 97%
“…However, during the last two decades, our knowledge on the ecology of several species in this family has dramatically increased. Different studies in Ireland have suggested that the deep areas of the Rockall Trough, Porcupine Bight, and slope systems off the northwest of Ireland, where bathymetry might be >1,000 m depth, may provide important habitats for beaked whales (Boisseau et al 2011, Wall et al 2013, Oudejans 2014, Rogan et al 2017. Despite the information compiled in these studies, knowledge on the ecology of True's beaked whales is poorly known and usually gleaned from the small number of strandings.…”
mentioning
confidence: 99%